2013
DOI: 10.1111/idh.12041
|View full text |Cite
|
Sign up to set email alerts
|

‘I take for granted that patients know’ – oral health professionals' strategies, considerations and methods when teaching patients how to use fluoride toothpaste

Abstract: The OHPs described toothbrushing with F toothpaste as very important, although the plaque removal perspective dominated. They did not focus on how to use F toothpaste, because they believed that knowledge about and appropriate behaviour concerning F toothpaste were already familiar to their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Strong evidence about the nature of the content of oral health promotion was derived from six studies, four of which were carried out in the UK and reported in five papers (3+ #bib1−), one in Israel (−), and one in Sweden (++) (see Table ). These studies explored the content of oral health promotion given in general practices, but none examined the effectiveness of the different oral health promotion messages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong evidence about the nature of the content of oral health promotion was derived from six studies, four of which were carried out in the UK and reported in five papers (3+ #bib1−), one in Israel (−), and one in Sweden (++) (see Table ). These studies explored the content of oral health promotion given in general practices, but none examined the effectiveness of the different oral health promotion messages.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the studies included in the review offered insights into the potential barriers and facilitators to effective oral health promotion. Strong evidence from 11 studies published in 12 papers (seven qualitative and four surveys (1++ #bib9+, 1−) described various barriers and facilitators to oral health promotion (see Table ). Strong evidence demonstrated that dentists gave messages which accorded with their own experiences and prejudices, and there was moderate evidence to suggest that the sender's belief in the credibility and effectiveness of OHP affected the likelihood of them conveying oral health messages to their patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study in Norway, Widstr€ om et al [32] found that chair-side preventive treatment measures delivered by dentists and dental hygienists were numerous but not fully in accordance with today's evidence-based practice. Jensen et al [33] reported that although the information given at the dental visit includes recommendations on toothbrushing, there are weaknesses concerning the fluoride concentration in toothpaste, rinsing procedures after brushing or toothpaste brushing techniques. As for the two oldest age groups who showed a particularly skewed caries distribution, this might indicate the need for a more selective preventive and treatment strategy for the subgroup with the highest need.…”
Section: Discussionmentioning
confidence: 99%
“…Even worse, only 10% report that they use fluoride toothpaste in an “optimal” way according to criteria established within the research team: a) two times a day, b) 2 minutes, c) apply a full brush, and d) do not rinse afterwards [ 56 ]. A recent questionnaire among patients of various age groups indicated that patients actually weren't told how to use fluoride and a qualitative study unveiled that dental professionals “took for granted that patients knew” [ 56 , 57 ]. Consequently, an important step in preventive practice is not only to focus on what to say, based on best available evidence, but also improve the skills on how to say it and make sure that the message is understood by the patients.…”
Section: Discussionmentioning
confidence: 99%